Syntenin-ALIX exosome biogenesis and budding into multivesicular bodies are controlled by ARF6 and PLD2 - Ghossoub, Rania; Lembo, Frédérique; Rubio, Aude; Gaillard, Carole Baron; Bouchet, Jérôme; Vitale, Nicolas; Slavík, Josef; Machala, Miroslav; Zimmermann, Pascale (Nature communications, 2014)
Exosomes are small vesicles that are secreted by cells and act as mediators of cell to cell communication. Because of their potential therapeutic significance, important efforts are being made towards characterizing exosomal contents. However, little is known about the mechanisms that govern exosome biogenesis. We have recently shown that the exosomal protein syntenin supports exosome production. Here we identify the small GTPase ADP ribosylation factor 6 (ARF6) and its effector phospholipase D2 (PLD2) as regulators of syntenin exosomes. ARF6 and PLD2 affect exosomes by controlling the budding of intraluminal vesicles (ILVs) into multivesicular bodies (MVBs). ARF6 also controls epidermal growth factor receptor degradation, suggesting a role in degradative MVBs. Yet ARF6 does not affect HIV-1 budding, excluding general effects on Endosomal Sorting Complexes Required for Transport. Our study highlights a novel pathway controlling ILV budding and exosome biogenesis and identifies an unexpected role for ARF6 in late endosomal trafficking.
Keywords: ADP-Ribosylation Factors; ADP-ribosylační faktory; Cell Line; exozómy; transport proteinů; Multivesicular Bodies; endozomální třídící komplexy pro transport; proteiny vázající vápník; HIV-1; ErbB Receptors; Syntenins; HIV infekce; synteniny; Cell Cycle Proteins; fosfolipasa D; proteiny buněčného cyklu; ADP-ribosylační faktor 6; Humans; Phospholipase D; Exosomes; erbB receptory; Calcium-Binding Proteins; Protein Transport; ADP-Ribosylation Factor 6; buněčné linie; Endosomal Sorting Complexes Required for Transport; HIV Infections; lidé; multivezikulární tělíska